Copper–nickel oxide thin film library reactively co-sputtered from a metallic sectioned cathode. Issue 1 (22nd November 2013) - Burgstaller, Wolfgang; Hafner, Martina; Voith, Michael; Mardare, Andrei Ionut; Hassel, Achim Walter
Abstract